Skating with the Statue of Liberty - Meyer, Susan, 1960- (Delacorte Press, 2016)
After having escaped with his family from Nazi-occupied France, Gustave finds a home in New York City, still worried about Marcel, his good friend who he left behind, and surprised to find bigotry in America, too.